Symbolism and Cultural Representation in Lomban Tradition in Jepara - Grasia Butsaina Tsaabita (Javanologi: International Journal of Javanese Studies, 2024)
The Lomban tradition in Jepara is a cultural celebration rich in symbolism and historical significance for the local community. This tradition is conducted as an expression of gratitude forthe bounty from the sea and a plea for safety in fishing activities. Over time, Lomban has undergone transformations in its execution and symbolic meanings. This research aims to uncover the symbolism within the elements of the Lomban tradition, such as the procession of offerings, traditional dances, and the use of other symbols, using approaches from culturalanthropology and semiotics. The research methods employed include qualitative data frominterviews, direct observations, and literature analysis to provide a deep understanding of the cultural values and beliefs of the Jepara community embedded in Lomban. The findings show that Lomban is not merely a customary ceremony but also a reflection of the harmoniousrelationship between humans and nature, playing a significant role in preserving local cultural identity. The implications of this research underscore the importance of preserving and honoring cultural traditions as an integral part of Indonesia's cultural heritage.